Effect of self-exploration program on the self-concept of a special group of female adolescents - Romasanta, Maria Victoria (Animo Repository, 1982)
Adolesence is a period when an individual is trying to come to terms with himself and his environment. It is a time of the final stages of development of a self-concept, the confirmation and integration of which will be crucial in determining the developing individual's adjustment and future maturity status. This study focused on the exploration of the self as a means to enhance the self-conocepts of emotionally-disturbed adolescents who have been identified, e.g. as having poor self-concepts. The researcher attempted to develop a Self-Exploration Program and conduct it in a special school setting because of the verbalized need for career-related programs which will give assistance to the students in their career development.This study attempred to investigate the effect of a Self-Exploration Program on the self-concept of the student-residents of a select special school.